Internationally - legal facilities of functioning of offshore financial centers - Товкун, І. М. (Problems of legality, 2013)
In the article investigated problems that can generate offshore financial centers and events sent to adjusting of activity of such centers. Essence, terms of activity, classification of world offshore financial centers, is considered. Drawn conclusion that Ukraine also must set forth the legal position through this question.